Field experiences for pre-service teachers post-COVID-19: structures required to support mental health - Adams, Megan; Rodriguez, Sanjuana; Ramirez, Karla; Jackson, Virginie; Garefino, Allison (Frontiers in Education, 2023)
This study investigates a supplemental field experience taking place on a university campus in the summer of 2021. The program includes linguistically, culturally, and socioeconomically marginalized children performing below grade level in reading. Pre-service teachers (PSTs) work with the children for four weeks, focusing on science-based literacy instruction. The initial findings of this case study were that lesson planning, teacher dispositions, and willingness to accept feedback are critical for PSTs. Additionally, a major concern in the findings is the increased evidence of mental health concerns for the children and PSTs. The findings indicate a need for focused training on social-emotional learning with special care relating to stressors caused by COVID-19. There must also be additional training for PSTs on explicit and detailed lesson plans, adjusting their own dispositions, and science-based literacy instruction taught in literacy blocks.